2003
DOI: 10.2337/diabetes.52.10.2490
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity, Insulin Secretion, and Abdominal Fat

Abstract: The relationship between insulin sensitivity and overall obesity is well established. However, there remains debate as to which of the fat depots, visceral abdominal tissue (VAT) or subcutaneous abdominal tissue (SAT), is of greater importance. Also, the relationship between fat distribution and insulin secretion is largely unknown. We studied S I , acute insulin response (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
199
4
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(225 citation statements)
references
References 44 publications
14
199
4
8
Order By: Relevance
“…Recently, we reported that fat localized in the pancreas was inversely associated with dynamic measures of b-cell function in non-diabetic men (7). Previous reports described an association of intra-abdominal fat with b-cell function (8,9); however, this was not confirmed by others (10)(11)(12). This seeming discrepancy may be due to the differences in populations studied and the methods by which b-cell function parameters were estimated.…”
Section: Introductioncontrasting
confidence: 47%
“…Recently, we reported that fat localized in the pancreas was inversely associated with dynamic measures of b-cell function in non-diabetic men (7). Previous reports described an association of intra-abdominal fat with b-cell function (8,9); however, this was not confirmed by others (10)(11)(12). This seeming discrepancy may be due to the differences in populations studied and the methods by which b-cell function parameters were estimated.…”
Section: Introductioncontrasting
confidence: 47%
“…These relationships are likely to be due to obesity-related disturbances of glucose metabolism. Especially the visceral component of abdominal fat is strongly associated with insulin resistance [17], and thereby with a reduced ability to metabolise the glucose load of an OGTT. Interestingly, BMI in itself did not explain sex differences in 2hPG levels.…”
Section: Discussionmentioning
confidence: 99%
“…The overflow hypothesis posits that, as the capacity of adipocytes to store fat is exceeded, lipids overflow into other tissues, particularly the liver and muscle [59]. Increasing levels of ectopic lipid infiltration correlate with insulin resistance and increase risk of type 2 diabetes [60,61]. Elevated free fatty acid levels, and the conversion of free fatty acids to long chain acyl CoA derivatives, results in reduced insulin signalling and glucose transport, as well as further insulin resistance in liver and muscle [62,63].…”
Section: Clinical Pathophysiologymentioning
confidence: 99%